Counseling on Peatland Cultivation and Conservation to Pekanbaru State Forestry Vocational School Students: Penyuluhan Budidaya dan Konservasi Lahan Gambut pada Siswa SMK Kehutanan Negeri Pekanbaru - Yulia Setiani -; Ulfa Jusi; Neri Puspitasari; Silfia Rini; Riswanda Riswanda; Nurhasnah Nurhasnah (Universitas Lancang Kuning, 2023)
As an area that has the largest peatland on the island of Sumatra, various problems occured on peatlands in Riau Province. Forest fires that have an impact on public health and damage to the peat ecosystem due to inappropriate land use are examples of these problems. The Pekanbaru State Forestry Vocational School was chosen as a place for counseling, because this institution will produce forestry technical personnel who have environmental insight. It is necessary to give them material about the condition of peatlands in Riau Province where they are currently located. It is hoped that after they graduate, they will have sufficient insight and knowledge about peatland cultivation and conservation. Students seemed enthusiastic to see the presentation of the material as well as pictures and videos about the condition of peatlands in Riau. This was followed by a discussion forum and question and answer session. To measure the success of this activity, students fill out a short questionnaire containing questions about their understanding of the material provided. From the results of the questionnaire, students seemed to understand the importance of knowledge about peatlands, and were committed to maintaining their sustainability.